Solving Integral Equations by Common Fixed Point Theorems on Complex Partial b-Metric Spaces. (23rd June 2021) - Gnanaprakasam, Arul Joseph; Boulaaras, Salah Mahmoud; Mani, Gunaseelan; Abdalla, Mohamed; Alharbi, Asma
Abstract : In this paper, we prove some common fixed point theorems for rational contraction mapping on complex partial b -metric space. The presented results generalize and expand some of the literature's well-known results. We also explore some of the applications of our key results.